The operations of credit unions : are they viable in Iceland - Hrafn Splidt Þorvaldsson 2000-; Kristófer Björn Ólason Proppé 1993- (2022)
This paper explores the possibility that credit unions could be established and successfully operated in Iceland in light of low trust in the Icelandic banking system and interest in a community bank. Limited research has been conducted on the possibility. The research was done by analyzing what makes credit unions successful in the United States of America and laying out the basics of the Icelandic banking system, and exploring if they are compatible. The comparison showed that it is unlikely the Icelandic market could support a credit union.